2019
DOI: 10.1016/j.pmedr.2019.101007
|View full text |Cite|
|
Sign up to set email alerts
|

Congestive heart failure-related hospital deaths across the urban-rural continuum in the United States

Abstract: Congestive heart failure (CHF) is a growing public health problem that affects nearly 6.5 million individuals nationwide. Access to quality outpatient care and disease management programs has been shown to improve disease treatment and prognosis. Rural populations face unique challenges in the availability and accessibility of quality cardiovascular care. In 2018, we conducted a pooled cross-sectional analysis of the Nationwide Inpatient Sample (NIS) for 2009–2014 to examine recent trends in CHF-related hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Residents of rural communities in the West (OR, 1.47), Midwest (OR, 1.30), and South (OR, 1.21) have higher mortality risk during HF hospitalizations compared with residents of large metropolitan areas. 77…”
Section: Cardiomyopathy and Heart Failurementioning
confidence: 99%
“…Residents of rural communities in the West (OR, 1.47), Midwest (OR, 1.30), and South (OR, 1.21) have higher mortality risk during HF hospitalizations compared with residents of large metropolitan areas. 77…”
Section: Cardiomyopathy and Heart Failurementioning
confidence: 99%
“…Prior research on HF within rural communities has focused mainly on mortality outcomes . However, research on HF incidence among rural residents within the United States is relatively limited.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research identified that HF mortality was increased among rural residents [8][9][10]29 ; our results bring new knowledge to this domain by demonstrating that rural residents have a higher rate of HF incidence, with race-sex variation. Our results resonate with the call for primary prevention as a strategy to reduce HF health inequities put forth by Youmans et al 48 and provide important practical strategies to do so.…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…With reduced access to care, rural residents with these conditions are at greater risk of death than their urban counterparts. 36 , 37 Mergers can allow partnerships with urban hospitals to facilitate implementation of clinical pathways and protocols for improving patient outcomes. 38 Through mergers, rural hospitals can also gain access to capital investment in electronic health records and clinical decision support systems for enhancing technological capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure and pneumonia are high-volume conditions in rural areas with aging populations, and ensuring timely initial evaluation and treatment for acute stroke is particularly challenging. With reduced access to care, rural residents with these conditions are at greater risk of death than their urban counterparts . Mergers can allow partnerships with urban hospitals to facilitate implementation of clinical pathways and protocols for improving patient outcomes .…”
Section: Discussionmentioning
confidence: 99%